Development of a new single-phase field excitation flux switching motor topology with segmental rotor - Omar, Mohd Fairoz (2016)
Diverse topology of three-phase and single-phase Field Excitation Flux Switching Machines (FEFSMs) that have been developed recently have several advantages such as variable flux capability and the single piece structure of rotor suitable for high-speed applications. However, a salient rotor structure has led to a longer flux path resulting in high flux leakage and higher rotor weight. Meanwhile, overlap windings between armature and Field Excitation Coil (FEC) have caused the problems of high end coil increased size of motor and high copper losses. Therefore, a new topology of singlephase non-overlap windings 12S-6P FEFSM segmented rotor with the advantages of less weight and non-overlap between armature coil and FEC windings is presented. The design, flux linkage, back-EMF, cogging torque, average torque, speed, and power of this new topology are investigated by JMAG-Designer via a 2D-FEA. As a results the proposed motor has achieved torque and power of 0.91Nm and 293W, respectively. To prove the simulation result based on 2D-FEA, experimental test is performed and the armature back-EMF was observed with FE current of 4A is supplied. Finally, at the speed of 500 rpm and 3000 rpm, the back-EMF is 2.75 V and 16.13 V, respectively. The simulation results showed reasonable agreement with the experimental results, approximately difference range from 4.9% to 7.4%.